English The effectiveness of a group counseling program in positive psychology in reducing anxiety and depression and improving the quality of life among high school students - Alrawahneh, Faten (مجلة جامعة الملك عبدالعزيز: العلوم التربوية والنفسية, 2025)
Substance abuse is one of the critical and acute public health problems, being related to various health, psychological, and life issues. It was found that narrative therapy is an effective intervention to reduce the psychological dysphoria caused by addiction. Objectives: The objectives of this research are defining whether narrative group therapy is a helpful instrument to reduce depression and anxiety in high school students with addiction and to improve the overall life quality of such students. Methods: The structured quasi-experimental design, with pretest-posttest conditions were selected; one group was experimental, receiving counseling, and the other was not. The total number of respondents was 70, students of high schools, in the age of 14-18 were selected. Results: The results showed the considerable decrease in anxiety, and depression, in the case of the experimental group ( p < 0.0001 in both cases), the gathered data allowed us to assume that the intervention was helpful. Conclusion: The present study demonstrated that treating students with addiction in the context of school through a positive psychology is a productive instrument to reduce trauma symptoms. Nevertheless, the intervention’s effect, in this case, was limited to the symptoms of depression and anxiety. In other words, the present study showed that although the considered treatment is an effective way to cope with some mental health issues, the outcomes of the lives of those receiving them are not improved seriously. It is suggested that an accompanied intervention is further developed as well.